FAKTOR-FAKTOR PENDORONG TERJADINYA HEGEMONI NEGARA TERHADAP PEREMPUAN DALAM PELAKSANAAN PROGRAM KELUARGA BERENCANA ( Studi Kasus di Kecamatan Tejakula, Kabupaten Buleleng Bali) - Ni Nyoman Sukeni (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2009)
Family planning program has been designated to be gender awareness, but in practicethere are state hegemony against women happened, makes women participated higher thanmen in according to reach program target. This is happened pushed by several factor such asideology factor, contraception devices supply, economy factor, location of programsocialization factor, and state policy factor. To avoid women from state hegemony herebycan be advised to provided a balance suplly of contraception devices between women andmen, and also on their socialization.